Hexamethonium reverses the lethal cardiopulmonary damages in a rat model of brainstem lesions mimicking fatal enterovirus 71 encephalitis - Lu, Wen-Hsien; Hsieh, Kai-Sheng; Lu, Pei-Jung; Wu, Yi-Shan; Ho, Wen-Yu; Lai, Chi-Cheng; Wang, Jyh-Seng; Ger, Luo-Ping; Hsiao, Michael; Tseng, Ching-Jiunn (Critical care medicine, 2013)
Among enterovirus 71 infections, brainstem encephalitis progressing abruptly to cardiac dysfunction and pulmonary edema causes rapid death within several hours. However, no currently known early indicators and treatments can monitor or prevent the unexpectedly fulminant course. We investigate the possible mechanisms and treatment of fatal enterovirus 71 infections to prevent the abrupt progression to cardiac dysfunction and pulmonary edema by using an animal model. Treatment study. Research laboratory. Sprague-Dawley rats. We microinjected 6-hydroxydopamine or vitamin C into nucleus tractus solitarii of the rat and evaluated the cardiopulmonary changes after treatment with ganglionic blocker. The time course of changes in the heart and lungs of rats with brainstem lesions were investigated. Rats were administered 6-hydroxydopamine to induce brainstem lesions, causing acute hypertension in 10 minutes and acute elevations of catecholamines accompanied by acute cardiac dysfunction and increased strong expressions of connexin 43 gap junction protein in heart and lung specimens by immunohistochemical staining within 3 hours. Severe pulmonary hemorrhagic edema was produced within 6 hours, and the rats expired rapidly within 7 hours. After hexamethonium treatment, it was found that the acute hypertension induced by 6-hydroxydopamine lesions was immediately reversed and the acute high rise of catecholamine serum level was significantly attenuated within 3 hours, accompanied by preserved cardiac output and decreased expressions of connexin 43 in the heart and lungs. No pulmonary edema occurred and the rats survived for more than 14 hours. Early hexamethonium treatment attenuates acute excessive release of catecholamines to prevent cardiac dysfunction and pulmonary edema for increasing survival rate.